Perancangan Sistem Informasi Kepegawaian Berbasis Web Pada Desa Muktiwari - Ratih Dwi Asworowati; Anus Wuryanto; Dede Mustomi; Rini Pahmawati Simangunsong (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The village government is now increasingly advanced and smooth with the help of various kinds of technology ranging from applications and other supports. The computer is one of the tools that makes it easier in the form of making software and hardware.At this time, Muktiwari village is still conducting data collection manually, specifically for storing personnel data so that there is a high possibility of data errors, delays in the process of searching for employee data and the availability of required data. The method used in this study is direct observation of the administrative staff responsible for the data system,apart from field research, the author also conducts a literature study, namely by collecting sources relevant to the problems that occur. The design of this personnel information system will also use software design with a prototype model.The purpose of designing this system is to simplify the work process of employees and reduce repetitive performance, so that employee data can be stored neatly if at any time data is needed. The results of the design of the Muktiwari village staffing system will be able to increase efficiency and effectively improve the shortcomings of the existing system.